Analisis Optimalisasi dan Evaluasi Pelayanan Pada Mal Peyanan Publik Merdeka Kota Malang - Sekarsari, Retno Wulan; Anadza, Hirshi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Wiraraja, Sumenep, 2023)
Abstract The purpose of this research is to find out and analyze the optimization of public services in the city of Malang. Identification of the problem in this study regarding the satisfaction of service users at Public Service Malls (MPP) towards public services in Malang City. Researchers use public service theory, with supporting theories as follows: public service principles, public service standards, and public service quality. Researchers also use the theory of the Public Service Mall which consists of administrative functions. All of these theories are needed to evaluate existing services. The methodology used is a mixed method that focuses on analyzing and evaluating the effectiveness of Public Service Mall services in Malang City and optimizing the public communication of the City Government of Malang regarding the service program at the Public Service Mall. The results of this study are thatthe Community Satisfaction Index for public services at MPP Merdeka is in line with the levelof trust, support and community participation which is also good. Malang City Government communication is carried out through various YouTube channels, government agency websites, Twitter and socialization through the village which is reported by the mass media and online. MPP's communication content on various YouTube channels contains adequate information and tends to be one-way only. But the management of social media is still unresponsive so that the engagement is very weak. Utilization of publication space in MPP has not been done optimally. Keywords: Optimization, Evaluation, Service, Public. Abstrak Tujuan dilaksanakanya penelitian ini adalah untuk mengetahui menganalisa optimalisasi dari Pelayanan Publik yang telah diberikan di Kota Malang. Identifikasi masalah dalam penelitian ini adalah tentang kepuasan pengguna layanan di Mal Pelayanan Publik (MPP) terhadap pelayanan publik di Kota Malang. Peneliti menggunakan teori pelayanan publik, dengan teori pendukung yaitu sebagai berikut: asas pelayana, standar pelayanan publik, dan kualitas pelayanan publik. Peneliti juga menggunakan teori Mall Pelayanan Publik yang terdiri dari fungsi penyelenggaraan, prinsip pelayanan, tahapan pembentukan, dan proses penyelenggaraannya. Semua teori tersebut sangat dibutuhkan untuk mengevaluasi pelayanan yang ada. Metodologi yang digunakan adalah metode campuran yang terfokus untuk menganalisis dan evaluasi efektifitas pelayanan Mal Pelayanan Publik di Kota Malang dan optimalisasi dalam komunikasi publik Pemerintah Kota Malang terkait program yang ada di mall pelayanan Publik. Hasil dari penelitian ini adalah. Indeks Kepuasan Masyarakat pada layanan publik di MPP Merdeka mendapat sejalan dengan tingkat kepercayaan, dukungan, melalui berbagai channel: website perangkat daerah terkait & twitter dan sosialisasi melalui kelurahan yang diberitakan media massa serta online. Konten komunikasi MPP di berbagai channel mengandung informasi yang memadai dan cenderung satu arah saja. Tetapi pada pengelolaan sosial media masih kurang responsif sehingga engagementnya sangat lemah. Pemanfaatan ruang publikasi di MPP belum dilakukan secara optimal. Kata Kunci: Optimalisasi, Evaluasi, Pelayanan, Publik.